Pengaruh Harga dan Promosi terhadap Minat Beli Ulang Konsumen pada Jelita Cosmetik Tamansiswa Yogyakarta - Vika Irma Safitri; Nayang Istiqomah; Kristiana Sri Utami (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The aim of this research is to examine how much influence pricing and promotional activities have on consumers' decisions to repurchase Jelita Cosmetic products in the Tamansiswa area of Yogyakarta. In the face of intensifying business competition, adopting the right marketing strategy becomes increasingly vital. As the business environment grows more competitive, choosing an effective marketing approach is a key factor for success. Indonesia’s beauty sector has seen remarkable growth in recent years. Since its inception in 2005, Jelita Cosmetic has managed to capture consumer attention by offering competitive prices and running consistent promotional campaigns through social media and e-commerce channels. This research employs a quantitative approach by gathering data through surveys conducted with 65 customers of Jelita Cosmetic. The data was analyzed using multiple linear regression and supported by validity and reliability tests. The research findings reveal that both price and promotion have a positive and significant effect on consumer repurchase intentions, both individually and collectively. Approximately 58.4% of the variance in repurchase interest is accounted for by the two independent variables studied, with the remaining 41.6% attributed to other factors beyond the scope of this study. These results offermeaningful insights into how effective marketing strategies can be applied within the beauty industry.